2016
DOI: 10.1016/j.cortex.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The GABAB receptor agonist, baclofen, contributes to three distinct varieties of amnesia in the human brain – A detailed case report

Abstract: We describe a patient in whom long-term, therapeutic infusion of the selective gamma-amino-butyric acid type B (GABAB) receptor agonist, baclofen, into the cerebrospinal fluid gave rise to three distinct varieties of memory impairment: i) repeated, short periods of severe global amnesia, ii) accelerated long-term forgetting, evident over intervals of days and iii) a loss of established autobiographical memories. This pattern of impairment has been reported in patients with temporal lobe epilepsy, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Instead, many studies default to reporting only the total external details metric without considering their constituent elements in more detail (e.g., Benjamin, Cifelli, Garrard, Caine, & Jones, 2015;Spreng et al, 2018), with others reporting only selective subcategories (e.g., Mair, Poirier, & Conway, 2017;Rensen et al, 2017), or failing to examine external details entirely (e.g., Baron & Bluck, 2009;Crete-Nishihata et al, 2012). In addition to the inconsistent reporting of external details, a common tendency to consider the aggregated external details category as uniformly 'semantic' pervades the literature (e.g., Ally, Hussey, & Donahue, 2013;Zeman et al, 2016). While no such claim was made in the original AI validation study (Levine et al, 2002), findings that elevated external details in healthy older adults are primarily driven by increased semantic information (e.g., Levine et al, 2002;St.…”
mentioning
confidence: 99%
“…Instead, many studies default to reporting only the total external details metric without considering their constituent elements in more detail (e.g., Benjamin, Cifelli, Garrard, Caine, & Jones, 2015;Spreng et al, 2018), with others reporting only selective subcategories (e.g., Mair, Poirier, & Conway, 2017;Rensen et al, 2017), or failing to examine external details entirely (e.g., Baron & Bluck, 2009;Crete-Nishihata et al, 2012). In addition to the inconsistent reporting of external details, a common tendency to consider the aggregated external details category as uniformly 'semantic' pervades the literature (e.g., Ally, Hussey, & Donahue, 2013;Zeman et al, 2016). While no such claim was made in the original AI validation study (Levine et al, 2002), findings that elevated external details in healthy older adults are primarily driven by increased semantic information (e.g., Levine et al, 2002;St.…”
mentioning
confidence: 99%
“…In our second study, we investigated the prognosis of ALF and ABM in a case of Baclofen-induced memory disturbance. A full description of the case history and original study can be found in Zeman et al (2016) . A summary is provided below.…”
Section: Study 2 – Baclofen Case Report: Alf Follow-upmentioning
confidence: 99%
“…By conducting a series of tailored memory experiments, we clearly documented the presence of ALF while CS was ON baclofen (in 2012) and the cessation of ALF after CS withdrew from Baclofen (i.e. OFF baclofen, in 2013) ( Zeman et al, 2016 ). Despite remission of her ALF, CS’s ability to retain recent autobiographical events remained impaired.…”
Section: Study 2 – Baclofen Case Report: Alf Follow-upmentioning
confidence: 99%
See 2 more Smart Citations